Survey of Cattle Feedlot Facilities in the High Plains Region of the United States - J. C. Simroth; D. U. Thomson; E. F. Schwandt; S. J. Bartle; C. K. Larson; C. D. Reinhardt (Kansas Agricultural Experiment Station Research Reports, 2017)
Defining the appropriate dimensions and type of feeding facilities for feedlot cattle fed in outdoor pens is important because the characteristics of these facilities have a significant impact on the performance, welfare, and health of cattle housed in those facilities, as well as a considerable impact on the final cost of the project. Although multiple sources can be found in the literature that provide recommendations with regard to design of facilities to be used in outdoor feeding facilities for feedlot cattle, there are no published data that describe the dimensions and type of feeding facilities currently used by the feedlot industry in outdoor feeding operations. Thus, the objective of this survey was to obtain descriptive data regarding outdoor cattle feeding facilities currently used by feedlots in the High Plains region of the United States.
Keywords: feedlot; facilities; survey